SOME ASPECTS OF EFFECTIVE ORGANISING OF TRAINING BASED ON MEDIA STUDY IN MEDICAL EDUCATION (Scientific journal of the Fergana State University, 2024)
This article highlights and analyzes the issues of developing students' media competence through teaching the subject of medical information technology.